2010
DOI: 10.1021/jp910656g
|View full text |Cite
|
Sign up to set email alerts
|

Nanotoxicity and Spectroscopy Studies of Silver Nanoparticle: Calf Thymus DNA and K562 as Targets

Abstract: The interaction between silver nanoparticle and calf thymus DNA was studied by UV−visible, fluorescence, and far UV circular dichroism (CD) spectroscopies at a physiologic temperature of 37 °C. By the analysis of UV−visible titration and thermal denaturation studies of DNA, it was found that silver nanoparticle can form a new complex with double-helical DNA and increase the T m value of DNA. This kind of binding may cause a slight change of the conformation of DNA. The fluorescence emission spectra of intercal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(117 citation statements)
references
References 33 publications
4
109
0
3
Order By: Relevance
“…Sperling and Parak demonstrated that the chemical nature of the solvent affects the extent of aggregation of the micelle into colloidal nanostructures. 9 Calcium carbonate, CaCO 3 , is found in nature in many morphological forms, and sea life has proved particularly adept at growing it into a variety of shapes. Recent laboratory-based studies have revealed that carbonates can be grown into different structures (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperling and Parak demonstrated that the chemical nature of the solvent affects the extent of aggregation of the micelle into colloidal nanostructures. 9 Calcium carbonate, CaCO 3 , is found in nature in many morphological forms, and sea life has proved particularly adept at growing it into a variety of shapes. Recent laboratory-based studies have revealed that carbonates can be grown into different structures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…22 Experiments on alkyl sulfonate and alkyl phenate stabilized nanoparticles predict a predominantly amorphous core, 22-24 a conclusion supported by classical Molecular Dynamics (MD) simulations of Quigley and Rodger. 25 Kobylyansky found that CaCO 3 nanoparticles stabilized by sulfonate-based surfactants display faster neutralization properties than the corresponding phenate and salicylate systems. 21 There is widespread interest in establishing chemical architecture-property relationships for these nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the interaction of a fluorescence compound with DNA provokes changes in its emission spectrum [45].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, hypochromism and red shift are associated with the intercalative binding mode between molecules and DNA [11] whereas hyperchromism is correlated with groove binding between host and guest [12]. Since the compounds 3a and 6a showed the band in the UV-range under identical experimental conditions, here we just discuss the apparent changing of UV bands of 3a and 6a when interacted with CT-DNA.…”
Section: Electronic Absorption Spectramentioning
confidence: 97%